DOES INDEPENDENT COMMISSIONER CONTRIBUTE TO DECREASE EARNINGS MANAGEMENT AND TAX AVOIDANCE ACTIVITIES - Zaman, Alfian Nur; Maharani, Arum Puspita; Firmansyah, Amrie (EQUITY, 2023)
This study examines the independent commissioner's role in moderating earnings management's effect on tax avoidance practices in the building construction industry. This study uses data from building construction sector companies listed on the Indonesia Stock Exchange during 2017-2020. Of the 15 companies observed, 42 samples were obtained using purposive sampling to be used in the study. They are processing data using regression analysis with cross-sectional data. The study results show that the company's earnings management positively affects tax avoidance activities carried out by building construction companies. Meanwhile, an independent commissioner does not affect the relationship between earnings management practices and corporate tax avoidance. Keywords: Corporate Governance, Earnings Quality, Tax Planning